2019
DOI: 10.3390/buildings9050120
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation of Corrosion-Defected RC Beam-Column Members Using Patch Repair Technique

Abstract: An experimental study was conducted to evaluate the efficiency of patch repair to rehabilitate corrosion-defected reinforced concrete (RC) beam-column members when exposed to bending moments and axial forces. Ten RC beam-column members were tested under combined constant axial force and four-point transverse load up to failure. Two levels of the constant axial force were applied at either 15 kN or 30 kN (i.e., 25% or 50% of the ultimate design load of the control specimen). The accelerated corrosion process wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Overall, beams rehabilitated using these three approaches show promising results, not only in terms of significant ultimate capacity improvement but also without compromising structural ductility significantly. The results obtained in this study appear to be consistent with the findings of Alwash et al [6] on RC beams reinforced with mortar, which provided less ductile performance, and the use of GFRP [24] as reinforcement material in critical beams, which had a greater impact on ductility compared to mortar.…”
Section: Performance Of Beams Ductilitysupporting
confidence: 91%
See 1 more Smart Citation
“…Overall, beams rehabilitated using these three approaches show promising results, not only in terms of significant ultimate capacity improvement but also without compromising structural ductility significantly. The results obtained in this study appear to be consistent with the findings of Alwash et al [6] on RC beams reinforced with mortar, which provided less ductile performance, and the use of GFRP [24] as reinforcement material in critical beams, which had a greater impact on ductility compared to mortar.…”
Section: Performance Of Beams Ductilitysupporting
confidence: 91%
“…Gergess et al [4] and Chalioris et al [5] focused on the repair of RC beams damaged to the point of yielding longitudinal reinforcing steel bars simulating RC structural elements in existing structures subjected to increased service loads. Alwash et al [6] rehabilitated reinforced concrete column-beam (RC) specimens that corroded when subjected to bending moments and axial forces. Corrosion reinforcement damage can be addressed by patching repair techniques and replacing the corroded steel reinforcement.…”
Section: Introductionmentioning
confidence: 99%
“…Beams that have been corroded on the steel reinforcement due to the influence of chloride attacks from the marine environment or due to the carbonation process will expand and cause longitudinal cracks around the concrete cover, resulting in spalling, as illustrated in Figure 3. This causes a decrease in the nominal moment capacity of reinforced concrete beams [8][9][10][11].…”
Section: Figure 1 Solid Waste From Construction Demolishingmentioning
confidence: 99%
“…The findings also showed that ECC was ineffective for preventing the diagonal shear crack in the joint area. Alwash et al [27] and Bossio et al [28] studied the corrosion of RC joints when exposed to bending moment and axial forces. Their study was oriented on the loss of integrity, a decrease of load-bearing capacity, stiffness, and serviceability due to corrosion, and the on joints' rehabilitation with the patch repair technique (PRT).…”
Section: Introductionmentioning
confidence: 99%